Inhibitory effect of carboplatin in combination with bevacizumab on human retinoblastoma in an in vitro and in vivo model - Zhang, Qi (Oncol Lett, 2017)
Retinoblastoma is the most common type of malignant intraocular tumor in children, and angiogenesis is required for tumor growth and expansion. The present study investigated whether use of the vascular endothelial growth factor inhibitor antibody bevacizumab can increase the inhibitory effect of carboplatin on human retinoblastoma Y79 cells. This was investigated using in vitro and in vivo models. Cell proliferation was assayed using a Cell Counting Kit-8 assay, which tested different concentrations of carboplatin in combination with bevacizumab. Cell apoptosis and cell cycle were analyzed using flow cytometry. Protein levels of related signaling pathway molecules were determined by western blotting. The present study used an intravitreal retinoblastoma mouse model for the in vivo study (n=40). Tumors were analyzed histologically. The present study revealed that combining bevacizumab and carboplatin in an in vitro culture of Y79 cells led to a higher inhibition of cellular proliferation than carboplatin alone (P<0.05). The drug combination caused increased apoptosis, and a greater inhibition of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) and mitogen activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathways. This combination also effectively inhibited tumor growth in vivo (P<0.05). These results demonstrate that a combination of carboplatin and bevacizumab results in a greater antitumor effect in advanced human retinoblastoma in vitro and in vivo by inhibiting the PI3K/Akt and MAPK/ERK pathways.